Declining Analysis of Service Function Area Irrigation Sragi Pekalongan Regency - Budhi Antoyo; Soedarsono Soedarsono; Moch Faiqun Ni'am (International Conference on Coastal and Delta Areas, 2017)
Irrigation Area Sragi is one of irrigation areas of central government authority with a standard acreage of 3426 ha and functional area of 3212 ha located in Pekalongan Regency. The availability of water and the water supply from the weir is sufficient but the downstream supply can not be met. The purpose of this research is to get index of irrigation network performance of Sragi Irrigation Area and priority scale of handling to decrease function of irrigation network service of Irrigation Area of Sragi. Descriptive approach method to collect information about the conditions that are happening on the Irrigation Network Dareah Irrigation Sragi Pekalongan Regency. The results are the variables of irrigation buildings, the implementation of water distribution of buildings in tapping buildings, anticipation of water loss, sedimentation in irrigation networks, human resources and water management affect the decline in service function D.I Sragi. The most influential variable to the decline of irrigation area service function is irrigation building variable which is shown by regression coefficient value equal to 0,106. Keywords: service function, irrigation area, Sragi